2018
DOI: 10.3168/jds.2017-13081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental calcium salts of palm oil and chromium-propionate on insulin sensitivity and productive and reproductive traits of mid- to late-lactating Holstein × Gir dairy cows consuming excessive energy

Abstract: This experiment compared insulin sensitivity, milk production, and reproductive outcomes in dairy cows consuming excessive energy during mid to late lactation and receiving in a 2 × 2 factorial design (1) concentrate based on ground corn (CRN; n = 20) or including 8% (DM basis) of Ca salts of palm oil (CSPO; n = 20), and (2) supplemented (n = 20) or not (n = 20) with 2.5 g/d of Cr-propionate. During the experiment (d 0-203), 40 multiparous, nonpregnant, lactating 3/4 Holstein × 1/4 Gir cows (initial days in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Calcium salts of palm oil increased the concentration of insulin and BHB in the blood, indicating energy generation by lipid metabolism. Supplementation with chromium propionate increased the concentration of NEFA and BHB, which are common ndings in a high metabolizable energy diet [25]. The use of chromium propionate days before parturition increases lipolysis [26].…”
Section: Ewesmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium salts of palm oil increased the concentration of insulin and BHB in the blood, indicating energy generation by lipid metabolism. Supplementation with chromium propionate increased the concentration of NEFA and BHB, which are common ndings in a high metabolizable energy diet [25]. The use of chromium propionate days before parturition increases lipolysis [26].…”
Section: Ewesmentioning
confidence: 99%
“…Therefore, the best energy use of the diet by the ewe fed either with CR or with PF may have increased the milk production of the ewes, which allowed better nutrition of the lambs and thus in uenced the weight at weaning and slaughter. The bene cial effect of chromium propionate or calcium salts of palm oil has already been proven with dairy cows [25].…”
Section: Performancementioning
confidence: 99%
“…Evans y Bowman (1992) reportaron que el picolinato de Cr incrementa la fluidez de la membrana celular promoviendo la internalización de la insulina e incrementando la sensibilidad celular a la glucosa, resultando en mayor tasa de absorción celular y menor concentración de glucosa sanguínea. Diversos estudios muestran claramente que la suplementación con Cr incrementa la tasa de depuración y reducen la vida media de glucosa sanguínea en cerdos (Amoikon et al, 1995;Matthews et al, 2001), aves (Noori et al, 2012) y rumiantes (Leiva et al, 2018;Bernhard et al, 2012;Kegley et al, 2000). El consumo de Cr también redujo el espesor de la grasa dorsal sin importar el peso al que inició la suplementación, lo que sugiere modificaciones del metabolismo lipídico en los cerdos suplementados.…”
Section: Características De La Canal Y Calidad De Carneunclassified
“…Starch is the main source of glucose for ruminants and is considered highly insulinogenic , nevertheless, high-energy diets may lead to decreased insulin sensitivity, and in dairy cows this negatively affects milk production and breast synthesis of milk constituents (LeBlanc, 2010), however, previous research with dairy cows showed that chromium propionate supplementation in high energy diets affected insulin and glucose concentrations, avoiding decreased insulin sensitivity (Leiva et al, 2015(Leiva et al, , 2018. These factors may be an explanation for the difference in weight between lambs from chromium propionatesupplemented mothers and lambs compared to starch-supplemented mothers, where STCRs were heavier, even though there was no statistical difference.…”
Section: Effect On Birthweight and Growth Ratementioning
confidence: 99%
“…Chromium acts in conjunction with insulin receptors on cells sensitive to this hormone, increasing glucose intake, improving the use of the energy supplied . It can also act as a modulator of the body fat of the offspring during pregnancy and lactation (Padmavathi et al, 2010) and for highenergy diets that can cause decreased insulin sensitivity, negatively affecting milk production in dairy cows (LeBlanc, 2010), chromium propionate supplementation in high-energy diets affected insulin and glucose concentrations, avoiding decreased insulin sensitivity (Leiva et al, 2015(Leiva et al, , 2018).…”
Section: Introductionmentioning
confidence: 99%